A Māori Model of Leadership Practice - Papesch, Te Rita (Te Kaharoa, 2021)
He Waka Hiringa (HWH) is a Masters of Applied Indigenous Knowledge offered as a programme of two years’ study by Te Wānanga o Aotearoa. The main pre-requisite for enrolment in to this graduate degree is for the student to be a master of their own practice, whatever that practice may be. In other words, they are already leaders in their own field of practice. My task is to help them clarify how they indigenise their practice; introduce them to academic processes to achieve the rangahau (research) around this and encourage them to create their own Models of Practice (MsOP) to guide them as they work with students or clients. In six years three cohorts of students have succesfully graduated through my encouragement in the development and approval of about 100 different new MsOP, each unique in its own way. These add to the use by graduates of HWH to models such as Whare Tapatoru ( Wi Te Tau Huata Snr. 1967, personal communication), Whare Tapawhā (Durie, M. 1984), Te Wheke (Pere, R. 1997) and Poutama Pōwhiri (Huata, P. 2011) to name a few well known MsOP. In terms of a Leadership MOP I have not seen a better model than that created by Te Wairere Te Pūāwaitanga o te Whakaaro Ngaia (my youngest child and daughter) to fulfil the requirements of her Masters in Management Communications and Te Reo Māori (Māori Language) graduate degree at The University of Waikato. I am going to use her MOP for leadership in competitive Kapa Haka[1] (Māori performing arts) as my model in this delivery with her permission. The title comes from a waiata-ā-ringa (action song) composed by one of her tuākana (older sisters), Te Ingo Karangaroa Ngaia, entitled ‘He Rākau Taumatua!’[2], for their whānau (family) kapa haka, Te Haona Kaha. [1] I use capital letters when talking about the art form and small letters when talking about a group that does the art form. [2] “He rākau taumatua” was first performed as a whakawātea by Te Haona Kaha kapa haka at the Tainui Waka Cultural Trust Regional Kapa Haka competitions in 2016.